Approaching the intrinsic exciton physics limit in two-dimensional semiconductor diodes - Chen, Peng; Atallah, Timothy L.; Lin, Zhaoyang; Wang, Peiqi; Lee, Sung-Joon; Xu, Junqing; Huang, Zhihong; Duan, Xidong; Ping, Yuan; Huang, Yu; Caram, Justin R.; Duan, Xiangfeng (Nature (London), 2021)
Two-dimensional (2D) semiconductors have attracted intense interest for their unique photophysical properties, including large exciton binding energies and strong gate tunability, which arise from their reduced dimensionality 1 – 5 . Despite considerable efforts, a disconnect persists between the fundamental photophysics in pristine 2D semiconductors and the practical device performances, which are often plagued by many extrinsic factors, including chemical disorder at the semiconductor–contact interface. Here, by using van der Waals contacts with minimal interfacial disorder, we suppress contact-induced Shockley–Read–Hall recombination and realize nearly intrinsic photophysics-dictated device performance in 2D semiconductor diodes. Using an electrostatic field in a split-gate geometry to independently modulate electron and hole doping in tungsten diselenide diodes, we discover an unusual peak in the short-circuit photocurrent at low charge densities. Time-resolved photoluminescence reveals a substantial decrease of the exciton lifetime from around 800 picoseconds in the charge-neutral regime to around 50 picoseconds at high doping densities owing to increased exciton–charge Auger recombination. Taken together, we show that an exciton-diffusion-limited model well explains the charge-density-dependent short-circuit photocurrent, a result further confirmed by scanning photocurrent microscopy. We thus demonstrate the fundamental role of exciton diffusion and two-body exciton–charge Auger recombination in 2D devices and highlight that the intrinsic photophysics of 2D semiconductors can be used to create more efficient optoelectronic devices. Two-dimensional transition metal dichalcogenide diodes with defect-free van der Waals contacts allows minimization of the extrinsic interfacial disorder-dominated recombination and access to the intrinsic excitonic behaviour in two-dimensional semiconductor devices.